2013
DOI: 10.1258/ar.2012.120254
|View full text |Cite
|
Sign up to set email alerts
|

A proposed protocol for acceptance and constancy control of computed tomography systems: A Nordic Association for Clinical Physics (NACP) work group report

Abstract: Based on international references and medical physicists' practical experiences, a comprehensive QA protocol for CT systems is proposed, including both acceptance and constancy tests. The protocol may serve as a reference for medical physicists in the Nordic countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…This was in accordance with the tolerances defined by the manufacturer and is also what the Nordic Association of Clinical Physics (NACP) and ACR recommend 1 , 11 …”
Section: Methodssupporting
confidence: 88%
See 3 more Smart Citations
“…This was in accordance with the tolerances defined by the manufacturer and is also what the Nordic Association of Clinical Physics (NACP) and ACR recommend 1 , 11 …”
Section: Methodssupporting
confidence: 88%
“…The CT number tolerance used during annual quality controls at the hospital is ± 4 HU for water and ± 10 HU for air. These are the same values as those recommended by the NACP and IEC 4 , 11 . As in the case with image noise discussed in the previous section, the automated definition of the ROI in this work resulted in a very stable estimate of the CT number of water and a reduction of the tolerance was possible.…”
Section: Methodsmentioning
confidence: 60%
See 2 more Smart Citations
“…The Nordic guidance on CT QA (13) lists CT AEC testing as an optional test and it is suggested that a cone‐shaped or anthropomorphic phantom could be used to assess the functionality of the AEC system, via noise measurements along the length of the phantom. CT AEC testing is one of the five major test areas in the Belgian CT QA protocol, (14) and the authors describe a methodology to allow the independent assessment of the longitudinal and rotational aspects of the AEC system.…”
Section: Introductionmentioning
confidence: 99%